New Kaposi's sarcoma-associated herpesvirus variant in men who have sex with men associated with severe pathologies. (13th April 2020) - Jary, Aude; Leducq, Valentin; Desire, Nathalie; Petit, Héloïse; Palich, Romain; Joly, Véronique; Canestri, Ana; Gothland, Adélie; Lambert-Niclot, Sidonie; Surgers, Laure; Amiel, Corinne; Descamps, Diane; et al.
Abstract: Background: Kaposi sarcoma (KS)–associated herpesvirus (KSHV) subtype depends mostly on patient origin. The current study aimed to assess KSHV diversity in a population of men who have sex with men (MSM) living in France. Methods: The study included 264 patients. In 65 MSM, including 57 human immunodeficiency virus (HIV)–infected men with KS, multicentric Castleman disease, or primary effusion lymphoma and 8 HIV-uninfected men receiving HIV preexposure prophylaxis (PrEP), we performed KSHV typing with K1 open reading frame Sanger and KSHV whole-genome sequencing. In 199 other patients, we performed real-time polymerase chain reaction screening for the new variant. Results: We found that 51% of KSHV-strains were subtype C (85% C3), and 33% were subtype A. Four patients with severe KSHV disease (2 with visceral KS, 1 with multicentric Castleman disease, and 1 with primary effusion lymphoma) and 1 asymptomatic PrEP user had a new variant resembling the Ugandan subtype F, but with different K1 open reading frame and KSHV whole-genome sequences and a different epidemiological context (MSM vs African population). Its prevalence was 4.5% in Caucasian MSM, and it was absent in other epidemiological groups. Conclusions: Subtype C predominated among MSM living in France. The new F variant was identified in Caucasian MSM and associated with severe KSHV disease, suggesting that subtype F could be split into F1 and F2 variants. Careful screening for this variant may be required in MSM, given the severe clinical presentation of associated diseases. Abstract : We identified a new Kaposi sarcoma–associated herpesvirus F variant in 5 Caucasian men who have sex with men. Careful screening may be required in this population, given the severe clinical presentation of associated diseases in the context of immunosuppression.